PENGEMBANGAN MULTIMEDIA PEMBELAJARAN IPS MATERI PAHLAWANKU TEMA 5 UNTUK SISWA KELAS IV SEKOLAH DASAR - Okta Gustina; Johan Priambudi; Ambyah Harjanto (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
This media development aims to produce a valid and effective learning media product as one of the learning resources for social science learning in grade 4 elementary school. The development of multimedia learning using ASSURE model which has 6 stages, namely: (1) student analysis, (2) determining learning objectives, (3) choosing methods, media and materials, (4) using media and materials, (5) encouraging student participation, (6) evaluation and improvement. The subject of this multimedia development of social studies is grade 4 elementary school students. The development of multimedia learning is declared valid for use in class IV IPS learning. This is obtained from the validation of media experts, material experts, individual students, small groups, large groups / klasikal. After the expert test and trial to students then conducted posttest that aims to find out the effectiveness of the use of this learning media. The test results obtained in the use of multimedia learning ips showed that the students managed to obtain grades above the established KKM. By demikan can be concluded that the development of multimedia learning ips is very effective to be used in conducting the learning process.